Signatures of a surviving helium-star companion in type Ia supernovae and constraints on the progenitor companion of SN 2011fe - Liu, Zhengwei; Röpke, Friedrich; Zeng, Yaotian (The astrophysical journal, 2022)
Single-degenerate (SD) binary systems composed of a white dwarf and a nondegenerate helium (He)-star companion have been proposed as the potential progenitors of Type Ia supernovae (SNe Ia). The He-star companions are expected to survive the SN Ia explosion in this SD progenitor model. In the present work, we map the surviving He-star companion models computed from our previous three-dimensional hydrodynamical simulations of ejecta-companion interaction into the one-dimensional stellar evolution code Modules for Experiments in Stellar Astrophysics to follow their long-term evolution to make predictions of their post-impact observational properties, which can be helpful in searches for such surviving He-star companions in future observations. By comparing with the very-late-epoch light curve of the best observed SN Ia, SN 2011fe, we find that our surviving He-star companions become significantly more luminous than SN 2011fe about 1000 days after maximum light. This suggests that an He star is very unlikely to be a companion to the progenitor of SN 2011fe.
Gesehen am 21.04.2022